THE ASSOCIATION BETWEEN SEVERITY OF MALOCCLUSSION WITH CARIES AMONG ADOLESCENTS STUDENTS OF SMKN 3 PARIAMAN - Kartika wulandari; Susi Susi (Andalas Dental Journal, 2016)
Malocclussion is one of the most common case in oral health and taking of third position after dental caries and periodontal disease. Malocclusion is a deviation form from normal occlussion. Malocclussion may caused problems in oral function, psychosocial problems and oral health problem, one of them is caries. Many of malocclusion character associated with severity of caries. The aim of this study was to know the association between severity of malocclussion with caries among adolescents students in SMKN 3 Pariaman. This study use observasional analytics with cross sectional approach. Sample were adolescents (16-19 years old) in SMKN 3 Pariaman.The sample were 75 students consisting of 15 students in each of grade complexity of malocclusion. The severity of malocclusion were identification based ICON (Index of Complexity, Outcome and Need) and caries was assess use DMF-T Index. The data were analyzed by Kruskal Walis test and Mann-Whitney test. Mean DMF-T students of SMKN 3 Pariaman was 3,00±1,716 (medium category). DMF-T indeks of malocclusion Easy was 1,466±1,407 (low category), Mild is 1,933±1,222 (low category), Moderate was 3,133±1,125 (medium category), Difficult was 4,066±1, (medium category), and Very Difficult was 4,400±1,298 (medium category). Mean of DMF-T indeks increased with increasing ICON of malocclusion. Statistical test result obtained by the p-value (p<0,05). There were association between severity of malocclussion with caries among adolescents students in SMKN 3 Pariaman. Key words : malocclussion, ICON, caries, DMF-T index